Penerapan Metode Complex Propotional Assessment dalam Penempatan Lokasi ATM Setor Tunai - Maret Sitanggang; Mesran Mesran (STMIK Budi Darma, 2022)
Competition in the field of bank services is one of them in the form of cash deposits. The need for cash deposit ATM machines is currently very influential to meet the increasing needs of the community, so the Bank needs to add cash deposit ATM machines in several densely populated locations that require financial transactions every day. In the addition of an ATM cash deposit machine location placement must be very careful because it involves public funds so it needs a high level of security. Decision support system is an appropriate concept to determine the location of cash deposit ATMs. Decision support system by applying the COPRAS (Complex Propotional Assessment) method can provide value to the location for the placement of cash deposit ATM machines where this method is a multi-criteria method in the decision making process where this method is used to select based on criteria from existing alternatives so that decision making can be done precisely and in accordance with what is needed. This system can provide the best location for ATMs, making it easier for officers to choose locations